FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA PEGAWAI NEGERI SIPIL DALAM PELAKSANAAN PELAYANAN PUBLIK PADA BADAN KEPEGAWAIAN - Gandeguai, Kartika; Niode, Burhan; H. Praktinjo, Maria; Pioh, Novie; Rumawas, Wehelmina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The main problem at the BKPP (Regional Personnel Board) of North Minahasa Regency is the low motivation of employees, influenced by factors such as delayed payment of allowances, political speculation in job promotions, unclean working conditions, and suboptimal implementation of training knowledge. The impact is evident in low work discipline, high levels of absenteeism, and strategic performance targets that have not been achieved. Solutions are needed to improve work motivation and address inhibiting factors to enhance public service effectiveness. This research aims to, first, assess the impact of compensation on the work motivation of Civil Servants at the BKPP of North Minahasa Regency in the context of public service. Second, identify the influence of promotions on employee motivation within the institution. Third, evaluate the relationship between the work environment and the work motivation of Civil Servants at the BKPP of North Minahasa Regency in the implementation of public services. Fourth, determine to what extent human resource development affects the work motivation of employees in the context of public service in the institution. The research method employed is explanatory with a quantitative approach, and data collection is done using questionnaires. The research sample involves 100 Civil Servants selected purposively. Data analysis is performed using SPSS to test validity, reliability, and hypotheses. The research results are expected to provide a better understanding of the factors influencing employee work motivation in the institution. The t-test analysis results show that the variables of compensation (X1), job promotion (X2), and the work environment (X3) significantly influence the work motivation (Y) of Civil Servants at the BKPP of North Minahasa Regency, with respective t-values of 2.389 (sig. 0.019), 2.270 (sig. 0.025), and 2.137 (sig. 0.035). However, the human resource development variable (X4) does not have a significant impact on work motivation, with a t-value of 0.494 (sig. 0.622). These results indicate that compensation, job promotion, and the work environment have a positive impact on work motivation, while human resource development does not significantly influence the work motivation of Civil Servants in the institution.